Social Exclusion of People Who Abstain from Mandatory COVID-19 Vaccination for Medical Reasons: A Contemporary Ethical Conflict - Grigoriadou, Virginia; Alifieri, Sofianna; Tsagdi, Sofia; Balatsou, Maria; Theologou, Kostas (Conatus - Journal of Philosophy, 2024)
The measures of obligatory vaccination against COVID-19 disease in Greece, have failed to cater to people, who for serious medical reasons, were prohibited by their private doctors to be vaccinated. This fact, however, leads to their unwilling social seclusion, since they cannot obtain the vaccination certificate that ensures access to all social activities. They are, therefore, faced with the dilemma of consenting to vaccination, disregarding possible health or even fatal consequences, or social exclusion and isolation. This research study aims to discuss this ethical conflict, between what is considered ethical for society in contrast to restriction of personal will and health. It wishes to rediscover the very essence of the commitment to protecting human rights-health and social well-being. This dilemma will be viewed and examined under the scope of core ethical values and principles met in Hippocrates’ oath and the fundamental ethical theory of Utilitarianism. The study will try, drawing from these ethical theories and definitions, to test these questions and conclude on what the indicative ethical choice is. The study wishes to propose suggestions of measures that can be taken to ensure equal operations for all citizens, based on medical ethics and self-disposition principles. It will also propose actions that should be put in the equation, sensitive groups. We feel that a balanced ethical approach that does not accentuate disparities within and among different groups, could ensure health equality, better social resilience, and commitment to effective prospective preparedness.